Sperm Motility Impairment in Free Spawning Invertebrates Under Near-Future Level of Ocean Acidification: Uncovering the Mechanism - Esposito, Maria Consiglia; Boni, Raffaele; Cuccaro, Alessia; Tosti, Elisabetta; Gallo, Alessandra (Frontiers in Marine Science, 2020)
Ocean acidification (OA) refers to the decrease in ocean water pH resulting from the increasing absorption of atmospheric CO2. This will cause changes in the ocean’s carbonate chemistry system with a resulting impact on reproduction of marine organisms. Reproduction is the fundamental process that allows the conservation of the species; in free-spawning marine invertebrates, this process is highly sensitive to changes in seawater quality and chemistry. To date, the majority of the studies concerned OA effects on reproduction has been focused on embryo and larval development. Despite several evidence for the impairment of reproductive success by environmental perturbations through altering gamete quality, sperm physiological responses to OA are poorly investigated. In this study, we evaluated the effects of exposure to acidified seawater (pH 7.8), which approximate the predicted global averages for oceanic surface waters at the end of this century, on sperm quality of the mussel Mytilus galloprovincialis and the ascidian Ciona robusta by evaluating several endpoints, such as motility, vitality, mitochondrial activity, oxidative state, and intracellular pH (pHi). Following sperm exposure to acidified seawater, the percentage of motile spermatozoa, mitochondrial activity and pHi decreased in comparison to the current seawater pH of 8.1, whereas vitality and oxidative state were unaffected by the low external pH in both the species. In broadcast spawners, a relationship between sperm intracellular pH and the initiation of motility are well known. Spermatozoa are immotile in the testes and motility is induced after the spermatozoa are released into seawater; the alkaline pH of seawater, in fact, increases the pHi activating motility and mitochondrial respiration. The results of this study suggest that the lowering of seawater pH as predicted to occur for 2100, through the inhibition of pHi increase, prevent sperm motility activation. Sperm motility is a key determinant of fertilization success; consequently, a corresponding drop in fertilization success would be expected with important implications for the fitness and the survival of marine invertebrates.